A ‘never before’ presentation of a common Mullerian abnormality - Bajaj, Bindu; Bajaj, Sunil Kumar; Bajaj, Sunil Kumar; Gaekwad, Harsha S.; Gaekwad, Harsha S.; Misra, Ritu; Misra, Ritu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Transvaginal septum is one of uncommon Mullerian anomalies which may lead to infertility. We all depend so often on HSG and MRI for investigating these infecund patients. Here we bring out how a distended vaginal cavity with contrast mimicked the uterine cavity on HSG misleading the clinician. The septum was missed on MRI too initially. A simple surgical correction and the patient was able to conceive in her very first cycle.